2007
DOI: 10.1002/joc.1582
|View full text |Cite
|
Sign up to set email alerts
|

Temperature change signals in northern Canada: convergence of statistical downscaling results using two driving GCMs

Abstract: Abstract:Coarse resolution global climate models (GCMs) have inherent difficulty simulating a reliable climate regime in coastal areas, as in northern Canada, where sea ice and snow cover are highly sensitive to fine-scale climate forcings. As a result, strong biases are present in GCM temperature regimes in this region, and the direct use of raw-GCM climate change signals at the local scale is problematic. However, fine resolution climate change information for use in impact studies can be obtained via statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
(60 reference statements)
1
34
0
Order By: Relevance
“…Comparisons between the SDSM and other downscaling methods have shown that the SDSM performed well in reproducing observed climate variability (Dibike and Coulibaly, 2005;Diaz-Nieto and Wilby, 2005;Khan et al, 2006;Wetterhall et al, 2006;Gachon and Dibike, 2007;Prudhomme and Davies, 2009). For example, Khan et al (2006) compared three downscaling methods, SDSM, Long Ashton Research Station Weather Generator (LARS-WG) model and an artificial neural network (ANN) for downscaling daily precipitation and maximum and minimum temperatures in a watershed of Canada and found SDSM performed the best.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparisons between the SDSM and other downscaling methods have shown that the SDSM performed well in reproducing observed climate variability (Dibike and Coulibaly, 2005;Diaz-Nieto and Wilby, 2005;Khan et al, 2006;Wetterhall et al, 2006;Gachon and Dibike, 2007;Prudhomme and Davies, 2009). For example, Khan et al (2006) compared three downscaling methods, SDSM, Long Ashton Research Station Weather Generator (LARS-WG) model and an artificial neural network (ANN) for downscaling daily precipitation and maximum and minimum temperatures in a watershed of Canada and found SDSM performed the best.…”
Section: Introductionmentioning
confidence: 95%
“…SDSM has been widely applied in SD studies for both climate variables and air quality variables (Diaz-Nieto and Wilby, 2005;Dibike and Coulibaly, 2005;Khan et al, 2006;Wetterhall et al, 2006;Gachon and Dibike, 2007;Prudhomme and Davies, 2009;Wise, 2009;and others), and has been recommended by the Canadian Climate Impacts and Scenarios (CCIS) project (http://www.cics.uvic.ca).…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour could be attributed to the only use of the coarse-scale NCEP/NCAR predictors in this procedure, without taking explicitly into account the regional-scale variables such as surface conditions or diabatic fluxes from the surface needed to capture all range of variability related to the occurrence of temperature extremes. These can come from nonlinear processes and feedbacks linked with frost and thaw conditions of the soil, and/or presence or absence of snow on the ground as indicated by Gachon and Dibike (2007) for northern Canada. As also noted in Hessami et al (2008), for the simulation of T max90p over eastern Quebec in Canada, outliers appear more often for the case of NCEP/NCARdriven conditions than for the GCM ones.…”
Section: Resultsmentioning
confidence: 99%
“…The main limitation of the SD techniques is related to the stationarity assumption of the SD model parameters (Wilby, 1997), which means that the statistical relationships developed for the current climate also hold under the different climatic conditions of future climate. Despite this constraint, SD methods have been commonly used in many different climate change impact studies (Wilby et al, 2002;Gachon and Dibike, 2007;Dibike et al, 2008;Nguyen and Nguyen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation using various SD methods to predict temperatures in central Europe indicated that Multiple Linear Regression (MLR) using one circulation-and one temperature-related variable produced the best predictions (Huth, 2002). Other studies have shown that SD is capable of capturing past low frequency climate variability (Dibike et al, 2008;Gachon & Dibike, 2007). The predictions of SD are, however, sensitive to the choice of reanalysis dataset used to train the regression.…”
Section: Introductionmentioning
confidence: 99%